Understanding patterns of food insecurity and family well‐being amid the COVID‐19 pandemic using daily surveys. Issue 5 (26th August 2021) - Steimle, Samantha; Gassman‐Pines, Anna; Johnson, Anna D.; Hines, Caitlin T.; Ryan, Rebecca M.
Abstract: This paper investigates economic and psychological hardship during the COVID‐19 pandemic among a diverse sample (61% Latinx; 16% White; 9% Black; 14% mixed/other race) of socioeconomically disadvantaged parents (90% mothers; mean age = 35 years) and their elementary school‐aged children (ages 4–11; 49% female) in rural Pennsylvania ( N  = 272). Families participating in a local food assistance program reported on food insecurity (FI) and parent and child mood and behavior daily from January to May 2020. Longitudinal models revealed that FI, negative parent and child mood, and child misbehavior significantly increased when schools closed; only FI and parent depression later decreased. FI decreased most among those who received the local food assistance program; Supplemental Nutrition Assistance Program receipt uniquely predicted decreases in child FI.